(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
This paper discusses John Keown’s argument whereby the available data concerning the practice of assisted dying in the Netherlands and in Oregon proves that the laws and guidelines adopted to prevent unlawful abuses are clearly ineffective. In his opinion, the main issues concern the following safeguards: request; type of suffering; consultation and reporting procedure. However, a close scrutiny of Keown’s empirical remarks will show that his conclusions are erroneous as they rely on a misinterpretation either of specific provisions (e.g. unbearable suffering in the Netherlands) or of the evidence taken into account (e.g. request and consultation in the Netherlands; reporting in Oregon). A correct understanding of both the regulatory regimes in place and the existing empirical data will demonstrate that in both countries there is a good rate of compliance with most of those safeguards; whilst it cannot be proved that a limited percentage of non-compliance with certain requirements (e.g. psychological consultation both in the Netherlands and in Oregon; and reporting in the Netherlands) has produced unlawful consequences for the patients,